1984
DOI: 10.1038/307233a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA for murine interleukin-3

Abstract: The cDNA sequence for murine interleukin-3, one of the colony stimulating factors that regulate haematopoiesis, codes for a polypeptide of 166 amino acids including a putative signal peptide. The predicted amino acid sequence indicates that formation of mature interleukin-3 involves proteolytic removal of not only the signal peptide but additional amino-terminal amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
1
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(110 citation statements)
references
References 35 publications
1
107
1
1
Order By: Relevance
“…The amount of FDC-Pl growth factor produced by the oocytes injected with mRNA from P388Dl or PUS-l.8 was 30-40 times less than observed with WEHl-3 mRNA. This is not surprising, since, under comparable conditions, WEHl-3 cells produce up to 1000 times more FDC-Pl growth factor activity than endotoxinstimulated PUS-l.8 cells being constitutive highlevel secretors of IL3 [12]. The enhanced expression of IL3 mRNA in WEHl-3 cells permitted the recent cloning of this factor using the oocyte translate/FDC-Pl cell assay system [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of FDC-Pl growth factor produced by the oocytes injected with mRNA from P388Dl or PUS-l.8 was 30-40 times less than observed with WEHl-3 mRNA. This is not surprising, since, under comparable conditions, WEHl-3 cells produce up to 1000 times more FDC-Pl growth factor activity than endotoxinstimulated PUS-l.8 cells being constitutive highlevel secretors of IL3 [12]. The enhanced expression of IL3 mRNA in WEHl-3 cells permitted the recent cloning of this factor using the oocyte translate/FDC-Pl cell assay system [12].…”
Section: Resultsmentioning
confidence: 99%
“…Having established optimal conditions for production, we showed that none of the FDC-Pl growth factor activity in PUS-l.8 (or P388Dl) conditioned medium could be attributed to IL3 since no activity was detectable using another factor-dependent cell line, 32D-C123, which responds to IL3 and interleukin 2, but not CSF-2 [6] (not shown). The absence of IL3 mRNA from P388Dl and PUS-l.8 cells has been confirmed using a specific cDNA probe [12] (KMS, DAH, in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…IL-3 is produced by mitogen or antigen-activated T cells, and it is involved in regulating the growth and differentiation of pluripotent stem cells leading to the production of all the major blood cell types [20]. It also has a broad range of biological activities and appears to be identical with a number of other factors named on the basis of their biological activities, such as multi-colony stimulating factor CSF, haematopoietic growth factor, mast cell growth factor and so forth [18].…”
Section: Introduction 2 Methods and Resultsmentioning
confidence: 99%
“…This plasmid has a Rous sarcoma virus promoter-driven IL-3 cDNA and a hygromycin Bresistance gene (from pY3 plasmid) in the pBMGNeo backbone. [26][27][28][29] Bicistronic mammalian expression vectors…”
Section: Plasmid Constructionmentioning
confidence: 99%